ANALISIS MDA FRAMEWORK PADA GAME POKEMON GO - Widyananda Putra, Ricky; Anissa, Jeanie (Kartala, 2023)
Technological developments are experiencing rapid progress in all fields, from the simple to the  increasingly sophisticated. Over time, technology has played a very important role in all fields, especially  entertainment. In the world of entertainment is one example of technological developments that  encourage the development of the game industry. Game is now known and still in demand, because it is a  form of game that is interesting and interactive for the players. This makes games an effective visual  medium for gathering experiences and information from user or player interactions. One game that  develops a form of interaction for its players is the game Pokemon GO, with the concept of augmented  reality (AR) this game provides more interactivity for users to explore real spaces in the virtual world. This  can bring a new experience for players to continue to enjoy the objects in the game. So the problem of this  research is how the game Pokemon GO can present an aesthetic interaction for the players. The purpose  of this study is to find out and explain the relationship between the aesthetics of interaction in game media  for players. In this study the theoretical approach used is the MDA (Mechanic, Dynamic, Aesthetic) model.  This approach describes each component that is interrelated, such as mechanics, dynamics, and aesthetics  in game media. Findings in research can indicate the type of interaction response that can be explored by  using game media. The conclusion drawn from this study is that in the future the MDA approach can be  used to analyze similar game mediums related to the presence of aesthetic interactions, especially in the  form of social relations, thus forming a social society within the community of game players.